EFEKTIVITAS PROGRAM BERSAMA KAMI PETUGAS LACAK KESEHATAN ROKAN DI PUSKESMAS ROKAN IV KOTO KABUPATEN ROKAN HULU - Lestari, Tista Rissa; RFS, Harapan Tua (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The effectiveness of the program with us, the Rokan health tracking officer at the Rokan IV Koto Health Center, Rokan Hulu Regency is an innovation activity of the Rokan IV Koto Health Center in overcoming the problem of the lack of community visits to check their health regularly at the Puskesmas and the lack of public awareness to behave in a clean and healthy life. This study aims to determine the effectiveness of the program with us Rokan health tracking officers at the Rokan IV Koto Health Center, and to determine the factors that hinder the effectiveness of the program with us Rokan health tracking officers at the Rokan IV Koto Health Center. This study uses a purposive sampling technique with a qualitative research type with a descriptive case study approach and the required data, both primary and secondary data obtained through observation, interviews and documentation, are then analyzed based on the research problem. The results of the study showed that the effectiveness of the program with us, the Rokan health tracking officer at the Rokan IV Koto Health Center, Rokan Hulu Regency was not optimal, this was due to several inhibiting factors such as the lack of facilities and infrastructure, and the low awareness of the community to carry out the program with us the Rokan health tracking officer in Rokan IV Koto Health Center. Keyword: Effectiveness, Program, Puskesmas